2020
DOI: 10.1002/btpr.2967
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing antibody production in a targeted integration host by optimization of subunit gene dosage and position

Abstract: Historically, therapeutic protein production in Chinese hamster ovary (CHO) cells has been accomplished by random integration (RI) of expression plasmids into the host cell genome. More recently, the development of targeted integration (TI) host cells has allowed for recombination of plasmid DNA into a predetermined genomic locus, eliminating one contributor to clone‐to‐clone variability. In this study, a TI host capable of simultaneously integrating two plasmids at the same genomic site was used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…However, WT Kozak Clone 50 contained approximately one additional copy of LC compared with Kozak Mix Clones 69 and 17 M (Figure 6c) and higher WT LC mRNA expression levels were observed accordingly (Figure 6d). These results establish a correlation between DNA copy number and transcript levels in the clones, as expected given the use of a targeted integration site for this work (Carver et al, 2020; Tadauchi et al, 2019). Remarkably, despite a very similar HC and LC mRNA level between Kozak Mix Clone 69 and 17 M, the clones show distinct protein expression profiles (Figure 6a), suggesting that the differences may be driven through a translational mechanism.…”
Section: Resultssupporting
confidence: 84%
“…However, WT Kozak Clone 50 contained approximately one additional copy of LC compared with Kozak Mix Clones 69 and 17 M (Figure 6c) and higher WT LC mRNA expression levels were observed accordingly (Figure 6d). These results establish a correlation between DNA copy number and transcript levels in the clones, as expected given the use of a targeted integration site for this work (Carver et al, 2020; Tadauchi et al, 2019). Remarkably, despite a very similar HC and LC mRNA level between Kozak Mix Clone 69 and 17 M, the clones show distinct protein expression profiles (Figure 6a), suggesting that the differences may be driven through a translational mechanism.…”
Section: Resultssupporting
confidence: 84%
“…Note that copy numbers and configurations of transgenes can affect protein expression in a manner that is dictated by the vector design and TI host(s) used. [ 20 ] Figure 6A depicts the overall subunit ratios tested for Molecule‐X, as the exact vector configurations cannot be disclosed. After pool evaluation for titer and aggregation levels, four of these pools were subjected to SCC (Figure 2A, left panel) from which more than 120 clones were evaluated in production culture with aggregation levels ranging between 4% and 25% (Figure 2A, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that CRISPR‐mediated integration of mCherry into CHO cells led to a more narrow range of fluorescence than clones created through random integration (Lee et al, 2015). In contrast, another study showed targeted integration of IgG resulted in clones with variable expression levels (Carver et al, 2020). Although most clones integrated near the Plec super‐enhancer locus had high transcript levels of IgG, the expression level did span over a range.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results shown in Figure 2D, where most genes are expressed at high but not necessarily at the highest levels. It has been reported that integration of a transgene into a predisposed transcriptionally active site identified in a high producer was highly active but could still be further enhanced by integrating two copies of the transgene into the same site (Carver et al, 2020).…”
Section: Discussionmentioning
confidence: 99%